Effectiveness of Fermented Coffee Cherry Liquid Extract on Preference of Coffee Berry Borer (Hypothenemus hampei Ferrari) at Coffee Plantation - Rasiska, Siska; Widiantini, Fitri; Nadhira, Nadhira (CROPSAVER, 2023)
Coffee Berry Borer (Hypothenemus hampei Ferrari) are the major pest of coffee crops that can cause damage up to 40 percent. One attempt to control CBB was to use an attractant from the coffee cherry, whose potential can be enhance by fermentation. Fermented coffee will produce metabolites, such as lactic acid, ethanol, and ethyl acetate, which can increase the complexity of the aroma. The study aims to determine the effect of the fermented coffee cherry liquid extract on  CBB attractiveness, assess the intensity of the CBB attack, and other insects trapped. The method used in this research is an experiment designed in groups at the site of people’s coffee plantations, Sindangsari Village, Sukasari-Sumedang District. The treatment in this study was a fermented coffee cherry liquid extract, with a volume of aquadest (150ml), 90ml, 120ml, and 150ml, thus obtaining 9 treatments, and each repeated 3 times. Other insects trapped was identified in Pest Laboratory-Universitas Padjadjaran. The results showed that the treatment of wet fermented coffee cherry liquid extract and the volume of 120ml and 150ml could trap CBB better than the other treatments, but did not affect the intensity of CBB attack on coffee plants. Other trapped insects were dominanted by the Coleoptera order of the Staphillinidae family that acted as predators and Diptera of the Drosophillidae family wich acted like herbivores. Thus, fermented coffee fruit liquid extract can be used as a CBB attractant, but its use for the purpose of controlling CBB needs to be well designed so that it does not have a negative impact on natural enemies or other non-target insects.